Kerusakan Metal Jalan Pada Auxiliary Engine di MT. Salmon Mustafa - Rivai, Rizal; Hermanto, Andy; Heriyawan, Mohammad Sapta; Suharto, Wakhid (Indonesian Journal of Marine Engineering, 2024)
Crank pin bearing consist of two plates with very smooth surfaces made from various metal layers with different hardness levels. This component is crucial because it supports the performance of the connecting rod on the crankshaft. It is installed to reduce friction occurring during combustion between the crankshaft and connecting rod. After combustion, the translational force of the piston is converted into rotational force on the crankshaft. The purpose of the research is to understand the factors, impacts, and mitigation efforts related to the damage of metal bearings on the auxiliary engine of MT. Salmon Mustafa. The research method used is qualitative descriptive with fishbone analysis techniques, where data is obtained from observations, interviews, and documentation. Interviews were conducted with the Chief Engineer, Second Engineer, and Third Engineer. The results of this study indicate that the causes of metal bearing damage on the auxiliary engine are suboptimal PMS implementation, inappropriate metal bearing components, decreased lubrication oil pressure, suboptimal lubrication oil cooling, presence of deposits on components, and corrosion or wear. The impacts of these factors include reduced performance of the auxiliary engine, imbalanced crankshaft rotation, and damage to the connecting rod and crankshaft. Efforts to prevent damage to the metal bearings of the auxiliary engine include increasing lubrication oil volume, cleaning the lubrication oil cooler, adjusting LO temperature and LO pressure, cleaning the lubrication oil filter, routine checking of the metal bearings of the auxiliary engine, and monitoring the running hours of the auxiliary engine lubrication oil.